2020
DOI: 10.1021/acs.jpca.9b11088
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Electron Attachment to 2,3,6,7,10,11-Hexabromotriphenylene

Abstract: pentabromotriphenylene (PBTP) were investigated by means of dissociative electron attachment spectroscopy (DEAS). The dominant decay channel of the transient molecular negative ions consists of elimination of Br − with resonances in the low electron energy region. Formation of long-lived parent anions with autodetachment lifetime τ a = 310 μs is observed at thermal electron energies. The adiabatic electron affinities, EA a = 1.12 ± 0.1 eV in HBTP and 1.09 ± 0.1 eV in PBTP, evaluated using a simple Arrhenius ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…DEA spectroscopy has proven to be a useful tool to study halogenated arenes. Thus, a recent work has reported EA a of 1.1±0.1 eV in hexa‐ and pentabromotriphenylenes [11] . Such electron withdrawing properties of brominated triphenylenes and electron‐capture‐induced debromination of its anions followed by oligomerization or cross‐coupling reactions make them promising scaffolds for material science applications in optoelectronics and discotic liquid crystals [12–15] …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…DEA spectroscopy has proven to be a useful tool to study halogenated arenes. Thus, a recent work has reported EA a of 1.1±0.1 eV in hexa‐ and pentabromotriphenylenes [11] . Such electron withdrawing properties of brominated triphenylenes and electron‐capture‐induced debromination of its anions followed by oligomerization or cross‐coupling reactions make them promising scaffolds for material science applications in optoelectronics and discotic liquid crystals [12–15] …”
Section: Introductionmentioning
confidence: 98%
“…Thus, a recent work has reported EA a of 1.1 � 0.1 eV in hexa-and pentabromotriphenylenes. [11] Such electron withdrawing properties of brominated triphenylenes and electron-capture-induced debromination of its anions followed by oligomerization or cross-coupling reactions make them promising scaffolds for material science applications in optoelectronics and discotic liquid crystals. [12][13][14][15] Recently, it has been shown that perhalogenated benzenes can be used as low-cost precursors for graphene-like films utilizable in energy-storage devices.…”
Section: Introductionmentioning
confidence: 99%